Techno Commercial Analysis of Liquefied Petroleum Gas Recovery From Natural Gas Using Aspen HYSYS - Ali, Usman; Zafar, Muhammad; Ahmed, Ashfaq; Zaman, Hafiz Kamran; Razzaq, Abdul; Daood, Syed Sheraz; Bashir, Muhammad; Park, Young-Kwon (Frontiers in Energy Research, 2021)
Liquefied petroleum gas is an alternative, relatively clean and a supreme source of energy, which is being used as a key component in the global energy supply. The international trade agreements and the chemical and non-chemical demand of liquefied petroleum gas with the increase in the world’s population have brought its production from the processing of natural gas to the limelight. During its processing, a variety of different components are extracted from it, including methane and ethane which remains in the bulk as natural gas. The objective of this research work is to find the capability of investigating the liquefied petroleum gas recovery performance to make the process economical by saving the processing cost and energy. The novelty of this work is to deal with the design and simulation of a liquefied petroleum gas plant using Aspen HYSYS. To make this process energy efficient and economical, different schemes of process alternatives were applied by reducing the sizes of the exchanger and other pieces of equipment. Three cases are studied in which feed is precooled by rerouting the stream and/or by repositioning of the chiller for the recovery of liquefied petroleum gas from natural gas by analyzing their cost and process parameters. The modelling and simulation base case and three different case studies are realized in Aspen HYSYS. It has been observed that case study 2 results in about 10% increase in LPG production where the chiller is repositioned in the separation section of the LPG production flowsheet. Case study 3 shows a maximum decrease in hot side utilities in the flowsheet of about 20% while 10 and 14% decreases are observed for case studies 1 and 2, respectively. Furthermore, economic analysis indicates about 18 and 22% in the capital cost for case studies 2 and 3, respectively, due to the lower size of process units. The outcome of this investigation is to present plenty of suggestions to improve the process efficiency and minimize the requirement to over design the plant components.